(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The article examines the problem of prosecution for copyright infringement (plagiarism) with the use of financial sanctions. The aim of the study is to identify the specific features of administrative liability, criminal liability, as well as civil liability for copyright infringement and their analysis from the standpoint of improving applied issues.